2019
DOI: 10.1186/s12889-018-6352-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual and family level factors associated with physical and mental health-related quality of life among people living with HIV in rural China

Abstract: BackgroundOne of the major challenges faced by people living with HIV (PLH) is the compromised quality of life due to the negative impact of HIV on their health. HIV/AIDS control effort should go beyond laboratory and lay more emphasis on improving the health-related quality of life (HRQoL) for PLH. The objective of this study is to evaluate the physical and mental HRQoL of PLH in rural China, and explore the relationship between HRQoL and individual- and family-level factors.MethodsA cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The lowest level of depressive symptoms and the best family functioning was reported by the family members with the highest income. Low family income represents inadequate healthcare resources and a lack of access to social services, which may influence a family's ability to cope with substance dependence-related financial and psychosocial burdens (Xiao et al, 2019). We have also observed gender disparity in depressive symptoms between female and male family members.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The lowest level of depressive symptoms and the best family functioning was reported by the family members with the highest income. Low family income represents inadequate healthcare resources and a lack of access to social services, which may influence a family's ability to cope with substance dependence-related financial and psychosocial burdens (Xiao et al, 2019). We have also observed gender disparity in depressive symptoms between female and male family members.…”
Section: Discussionmentioning
confidence: 63%
“…As suggested by the literature, family members' background characteristics, such as gender, age, income, and family role, are particularly salient to the outcome of interests (Noori et al, 2015;Shafer and Pace, 2015;Xiao et al, 2019). Thus, we collected family members' demographic characteristics, including age, gender, marital status, education, and annual family income (đồng).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found similar associations with demographic characteristics with the ones found in the present analysis. Female sex and advanced age have been widely associated with lower QoL [7][8][9]. Regarding advanced age, this association may be mediated by multiple comorbidities (and polypharmacy), physiological frailty, and cognitive dysfunction that are common in this population group [63].…”
Section: Discussionmentioning
confidence: 99%
“…Different sociodemographic and psychosocial factors are related to worse QoL in PLWHA, such as advanced age [7][8][9], lower income [7], female sex [7][8][9][10], death anxiety [11], substance use problems [9,12,13], tobacco use [9], and depression [9,12,14]. In contrast, younger age, higher educational level [15], and early adherence to combined antiretroviral therapy (cART) have been associated with better QoL [16,17].…”
Section: Introductionmentioning
confidence: 99%